การประเมินผลโครงการถนนปลอดถังขยะเทศบาลเมืองเมืองแกนพัฒนา อำเภอแม่แตง จังหวัดเชียงใหม่ - ณัฐวุฒิ วิทิตปริวรรต (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This independent study “An Evaluation of Without Garbage Bin Street Project of Muangkaen Pattana Mueang Municipality, Mae Taeng District, Chiang Mai Province” aims to study the effectiveness of Without Garbage Bin Street Project and collect problems and suggestions. The sample of this study was 320 households. In this study, the data collection process was done by a questionnaire. The analysis was done through frequency, percentage, mean, T – test, analysis of variance, and regression. The results of the study show that Without Garbage Bin Street Project of Muangkaen Pattana Mueang Municipality, Mae Taeng District, Chiang Mai Province has effectiveness of behavioral change in waste management. The behavior after implementation the project has different from before implementation the project significantly. The effectiveness of the participation of the people was in level of “high”. The factors that effected waste management significantly were age, marital status, occupation, and education level. The factors that effected Participation significantly were age, occupation, education, and the number of people living in the household. The knowhow about waste management effected waste management behavioral significantly, and the knowhow about waste management effected participation of the people significantly. The problems were lack of official visits, Equipment Breakdown, Lack of motivating the public to participate, and lack of funding to support.